Mycoremediation of lignocellulosic biorefinery sludge: A reinvigorating approach for organic contaminants remediation with simultaneous production of lignocellulolytic enzyme cocktail. (May 2022) - Kumar Vaidyanathan, Vinoth; Venkataraman, Swethaa; Senthil Kumar, P.; Sri Rajendran, Devi; Saikia, Kongkona; Karanam Rathankumar, Abiram; Cabana, Hubert; Varjani, Sunita
Highlights: Mycoremediation with concomitant enzymes production in sludge was analyzed. GYM media and rhamnolipids addition to sludge improved the mycoremediation process. 90% of 5 organic contaminants and 5 fermentation inhibitors were removed in sludge. Cost analysis for the enzyme cocktail production from sludge was analyzed. Abstract: This research work aims to valorize lignocellulosic biorefinery sludge with genetically engineered Trichoderma atroviride for simultaneous removal of organic contaminants, fermentation inhibitors, and lignocellulolytic enzyme cocktail production. Upon analysis, three phenolic compounds (42.6 ± 3.6 μg/g), two polycyclic aromatic hydrocarbons (0.42 ± 0.06 μg/g) and five fermentation inhibitors (2.5 ± 0.3 mg/g) were detected in the sludge. Bioaugmentation of sludge with 72 h-old T. atroviride (5%) results in the production of cellulase (21 U/g), xylanase (84 U/g), laccase (20 U/g), lignin peroxidase (14 U/g) and aryl alcohol oxidase (116 U/g), along with the concomitant removal of organic contaminants (phenol, 2, 4-dinitrophenol, pentchlorophenol, phenanthrene, benzo(a)pyrene) and fermentation inhibitors (furfural, 5-hydroxymethylfurfural, levulinic acid, ferulic acid, and catechol). Subsequently, the enrichment of sludge with nutrients and rhamnolipids enhanced the enzyme production by 5–6-fold and resulted in the removal of 85–95% of organic contaminants and fermentation inhibitors, which constitutes an eco-friendly process.